Mechanical properties of thermoplastic filament stitched carbon fiber reinforced composites - Sağlam, Gökçenur; Bedeloğlu, Ayşe (Bursa Teknik Üniversitesi, 2022)
In recent years, the use of composites has attracted great interest in both academia and industry, especially due to their lightness and mechanical properties. In this study, acrylonitrile butadiene styrene (ABS), poly(ethylene-co-methacrylic) acid (EMAA) and ethylene vinyl acetate (EVA) filaments were produced in a single screw extruder. The produced filaments were integrated into composite materials by stitching method, and then, the mechanical properties of the filaments and composites were investigated. According to the tensile test results, it is concluded that the stitching process affects the mechanical properties of the composite material. The strength of the composite material produced with EVA filament with a maximum diameter of 1mm increased by 23%. Apart from these, the composite materials produced with 1mm ABS and 0.6mm and 0.8mm EMAA filaments increased by an average of 15%. There was no significant change in the elongation of the composite material produced with 0.6mm, 0.8mm, and 1mm diameter filaments. The elongation of the composite material produced with only 1mm diameter ABS filament increased by 12%. The elongation values of the composite material prepared with 0.6mm diameter EMAA and EVA polymers decreased also by 15%.
Keywords: Engineering; Mühendislik